A rare cause of diffuse alveolar hemorrhage in a pediatric patient: thigh localization of INI1-deficient epithelioid sarcoma - Xiaolei Tang; Zhipeng Zhao; Xingfeng Yao; Chunju Zhou; Shuai Gong; Haiming Yang (Orphanet Journal of Rare Diseases)
Abstract Background Diffuse alveolar hemorrhage (DAH) is a group of rare but life-threatening conditions characterized by bleeding into the alveolar spaces, often associated with various etiologies. Epithelioid sarcoma (ES) is a rare and aggressive soft tissue sarcoma that has never been reported to be associated with DAH. Methods We report a rare case of ES in a pediatric patient presenting with DAH and intracranial hemorrhagic lesions. Diagnostic evaluations included high-resolution chest CT (HRCT), bronchoscopy, brain MRI, lung biopsy, Positron emission tomography - computed tomography (PET-CT), and biopsy of a mass in the right thigh. Fluorescence in situ hybridization was performed to detect SMARCB1 (INI1) gene deletion. Results A 13-year-old male presented with anemia and later developed hemoptysis with a decreased hemoglobin level. HRCT revealed bilateral ground-glass opacities consistent with DAH. Extensive autoimmune and infectious workups were all negative. Brain MRI demonstrated microhemorrhages. Despite corticosteroid therapy, the patient’s condition worsened. PET-CT identified a hypermetabolic soft tissue mass in the right thigh, which on histopathological examination was confirmed as INI1-deficient ES. FISH analysis confirmed INI1 deletion. Conclusion This case highlights the diagnostic challenges of INI1-deficient ES presenting with DAH and underscores the importance of considering malignancy in pediatric patients with atypical DAH. Multidisciplinary approaches, including advanced imaging and molecular diagnostics, are crucial for accurate diagnosis and management.